"Més Que Un Joc?": Sport and Contemporary Political Nationalism in Scotland and Catalonia. (June 2019) - Whigham, Stuart; Lopez-Gonzalez, Hibai; Ramon, Xavier
This article focuses upon two contexts which have arguably received the most academic and media attention with regard to the interconnection between sport and secessionist nationalism, Scotland and Catalonia, given that both "submerged nations" have held public referenda on the topic of independence/secession from the states of the United Kingdom and Spain, respectively. The analysis endeavors to draw parallels between the two contexts to critically examine the extent to which similarities and differences are evident in terms of the growth of political nationalism. Finally, the central discussion outlines the extent to which sport contributed to broader political developments in the recent campaigns for the establishment of independent Scottish and Catalan states, focusing upon the actions of prominent sporting personalities and organizations.